Integrative Medicine：A Characteristic China Model for Cancer Treatment - 李杰 林洪生 (Chinese journal of integrative medicine, 2011)
Integrative medicine（IM） has attracted increasing attention of the experts and patients around the world.Chinese medicine（CM）,as the important part of IM,has played an important role in the treatment of cancer.CM is practiced side by side with Western medicine in many of China＇s hospitals and clinics.On the basis of the review of the clinical practices and basic researches these years,we introduce the current situation and progress in integrative oncology in China,and show the main feature of CM approach in the cancer treatment.Furthermore,we also discuss the main problems limiting the progress of CM,and point out international collaboration will provide new opportunity to promote the development of IM in China.